2018
DOI: 10.1029/2017jf004327
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Energetic Rockfalls

Abstract: Extremely energetic rockfalls (EERs) are defined here as rockfalls for which a combination of both large volume and free fall height of hundreds of meters results in energy larger than about 80 GJ released in a short time. Examples include several events worldwide. In contrast to low energy rockfalls where block disintegration is limited, in EERs the impact after free fall causes immediate release of energy much like an explosion. The resulting air blast can snap trees hundreds of meters ahead of the fall area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 68 publications
(168 reference statements)
0
26
0
Order By: Relevance
“…There are many empirical/semiempirical and simplified physically based models describing the propagation of a failure mass, and these models have been applied to attempt the estimation of the travel distances of natural failure masses (De Blasio et al, 2018; Okura et al, 2000; Pastor et al, 2014; Strom & Abdrakhmatov, 2018). However, few analytical models consider the effects of fragmentation on the runout of the fragmenting failure mass (De Blasio et al, 2018; De Blasio & Crosta, 2015; Jaboyedoff et al, 2005; Ruiz‐Carulla et al, 2017). Here, we introduce the “fragmentation‐spreading model” proposed by Davies et al (1999), which is modified based on our experimental results, to describe the phenomenon of our experiments and explain the inverse relationship of the friction coefficient in the framework of the fragmentation process.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are many empirical/semiempirical and simplified physically based models describing the propagation of a failure mass, and these models have been applied to attempt the estimation of the travel distances of natural failure masses (De Blasio et al, 2018; Okura et al, 2000; Pastor et al, 2014; Strom & Abdrakhmatov, 2018). However, few analytical models consider the effects of fragmentation on the runout of the fragmenting failure mass (De Blasio et al, 2018; De Blasio & Crosta, 2015; Jaboyedoff et al, 2005; Ruiz‐Carulla et al, 2017). Here, we introduce the “fragmentation‐spreading model” proposed by Davies et al (1999), which is modified based on our experimental results, to describe the phenomenon of our experiments and explain the inverse relationship of the friction coefficient in the framework of the fragmentation process.…”
Section: Discussionmentioning
confidence: 99%
“…However, Davies, McSaveney, & Reznichenko (2019) and Davies, Reznichenko, & McSaveney (2019) inferred that only very small part of input energy is taken up as surface free energy in a newly created fragment surface (Savvova et al, 2015; Zdziennicka et al, 2009). For practicality, De Blasio et al (2018) proposed a semiexperimental method by which to obtain the fragmentation energy loss from the fragment size distribution, which indicated that, typically, 0.2–18% of the potential energy is consumed by fragmentation. The spreading coefficient due to fragmentation ( S f ) strongly depends on the energy consumption efficiency of fragmentation ( K f ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations